Response of potential activity, abundance and community composition of nitrite‐dependent anaerobic methanotrophs to long‐term fertilization in paddy soils. (7th July 2022) - Yang, Yuling; Shen, Lidong; Bai, Yanan; Zhao, Xu; Wang, Shuwei; Liu, Jiaqi; Liu, Xin; Tian, Maohui; Yang, Wangting; Jin, Jinghao; Huang, Hechen; Wu, Hongsheng
Abstract: The process of nitrite‐dependent anaerobic methane oxidation (n‐damo) catalysed by Candidatus Methylomirabilis oxyfera ( M . oxyfera )‐like bacteria is a novel pathway in regulating methane (CH4 ) emissions from paddy fields. Nitrogen fertilization is essential to improve rice yields and soil fertility; however, its effect on the n‐damo process is largely unknown. Here, the potential n‐damo activity, abundance and community composition of M . oxyfera ‐like bacteria were investigated in paddy fields under three long‐term (32 years) fertilization treatments, i.e. unfertilized control (CK), chemical fertilization (NPK) and straw incorporation with chemical fertilization (SNPK). Relative to the CK, both NPK and SNPK treatments significantly ( p  < 0.05) increased the potential n‐damo activity (88%–110%) and the abundance (52%–105%) of M . oxyfera ‐like bacteria. The variation of soil organic carbon (OrgC) content and inorganic nitrogen content caused by the input of chemical fertilizers and straw returning were identified as the key factors affecting the potential n‐damo activity and the abundance of M . oxyfera ‐like bacteria. However, the community composition and diversity of M . oxyfera ‐like bacteria did not change significantly by the input of fertilizers. Overall, our results provide the first evidence that long‐term fertilization greatly stimulates the n‐damo process, indicating its active role in controlling CH4 emissions from paddy fields.